Clinical CHaracteristics of Diabetic Ketoacidosis in Type 2 Diabetes Mellitus in Bangladesh Adult Patients - Hossain, Mohammad Zaid; Muhammad, Ali; Azad, Khan Abdul Kalam; Deb, Sudip Ranjan; Rahman, Md. Mostafizur; Anwar, ASM Tanim; Karmaker, Madhabi; Amin, Robed (Journal of Dhaka Medical College, 2013)
J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 131-139 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15299